2021
DOI: 10.1039/d0cc06693a
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurization-induced partially amorphous palladium sulfide nanosheets for highly efficient electrochemical hydrogen evolution

Abstract: Partially amorphous PdS was synthesized by sulfurizing crystalline palladium nanosheets via a facile method, displaying excellent activity and stability towards hydrogen evolution in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…Figure e shows the XPS spectrum of Pd 3d for S-Pdene. The Pd 3d peaks shifted to a higher energy position that was even more positive than the binding energy of the oxidation state of Pdene, which could be due to the formation of Pd sulfide (PdS x ). , In the XPS spectrum of S 2p, the main peak located at 162.66 eV was assigned to sulfide, indicating that the obtained metallene was substantially sulfurized, which was consistent with the analysis of the Pd 3d spectrum (Figure f). In addition to the major peak of sulfide, the other two peaks at 163.81 and 165.00 eV could be ascribed to bridging S 2 2– and apical S 2– , respectively, while the small peaks at higher binding energy position were related to oxidized S species on the surface. , The valence band of S-Pdene sample exhibited two major characteristics: (i) the decrease in bandwidth by 30% relative to that of the Pdene sample and (ii) the largest downward shift of the d-band with respect to the E F caused by the substantially reduced DOS at E F (Figure S8h).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Figure e shows the XPS spectrum of Pd 3d for S-Pdene. The Pd 3d peaks shifted to a higher energy position that was even more positive than the binding energy of the oxidation state of Pdene, which could be due to the formation of Pd sulfide (PdS x ). , In the XPS spectrum of S 2p, the main peak located at 162.66 eV was assigned to sulfide, indicating that the obtained metallene was substantially sulfurized, which was consistent with the analysis of the Pd 3d spectrum (Figure f). In addition to the major peak of sulfide, the other two peaks at 163.81 and 165.00 eV could be ascribed to bridging S 2 2– and apical S 2– , respectively, while the small peaks at higher binding energy position were related to oxidized S species on the surface. , The valence band of S-Pdene sample exhibited two major characteristics: (i) the decrease in bandwidth by 30% relative to that of the Pdene sample and (ii) the largest downward shift of the d-band with respect to the E F caused by the substantially reduced DOS at E F (Figure S8h).…”
Section: Resultssupporting
confidence: 81%
“…The Pd 3d peaks shifted to a higher energy position that was even more positive than the binding energy of the oxidation state of Pdene, which could be due to the formation of Pd sulfide (PdS x ). 13,42 In the XPS spectrum of S 2p, the main peak located at 162.66 eV was assigned to sulfide, indicating that the obtained metallene was substantially sulfurized, which was consistent with the analysis of the Pd 3d spectrum (Figure 2f). In addition to the major peak of sulfide, the other two peaks at 163.81 and 165.00 eV could be ascribed to bridging S 2 2− and apical S 2− , respectively, while the small peaks at higher binding energy position were related to oxidized S species on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, regulating the electronic structure of the Pd center can greatly boost the alkene selectivity or HER activity (20,21). In particular, sulfur modification has been proved to be an efficient route to improve the intrinsic activity and stability of Pd toward electrochemical HER and thermocatalytic organic hydrogenation reactions (22)(23)(24). In addition, high-curvature structures exhibit a high local electric field that increases the concentration of reactants or electrolytes around the tips, hence enhancing electrochemical CO 2 RR and HER performances (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proved that PdS x could be produced via a solvothermal method under a decreased reaction temperature. [112][113][114] As such, PdS x with different structures have been successfully synthesized via a facile one-pot hot solution sulfurization process. 112 In detail, Pd(acac) 2 and sulfur powder in OMA were heated to 320 °C and this was then mantained for 1 h. During this process, the in situ-generated Pd nanomaterials from Pd(acac) 2 reduction in OMA reacted with sulfur powder to form PdS x .…”
Section: Sulfur Atom-doped Pd Nanomaterialsmentioning
confidence: 99%
“…So far, many great efforts aimed to optimize H adsorption on the catalysts have been made. 54 As for Pd-based catalysts, it has been demonstrated that the strong Pd-H bonding could be weakened by doping with H, B, P or S. 24,82,109,113,136 For instance, Zou and co-workers found that the electrocatalytic activity of Pd could be greatly boosted by electrochemical H intercalation where the produced PdH x in situ could weaken the Pd-H bonding and thus facilitate hydrogen generation (Fig. 18).…”
Section: Pdl X For Hermentioning
confidence: 99%